Jingfang Granules for Diabetic Wound Healing: Insights from Network Pharmacology and Experimental Validation - Wang R; Wang Q; Liu M; Xiao H; Zhang G; Yao J; Liu M (Drug Design, Development and Therapy, 2025)
Rongrong Wang,1,2,* Qian Wang,1,2,* Mingfei Liu,3,* He Xiao,4 Guimin Zhang,5,6 Jingchun Yao,5,6 Ming Liu1,2 1Key Laboratory of Marine Drugs, Ministry of Education, School of Medicine and Pharmacy, Ocean University of China, Qingdao, 266003, People’s Republic of China; 2Laboratory for Marine Drugs and Bioproducts, Qingdao Marine Science and Technology Center, Qingdao, 266237, People’s Republic of China; 3School of Chinese Materia Medica, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of China; 4Experimental Research Center, China Academy of Chinese Medical Sciences, Beijing, 100700, People’s Republic of China; 5State Key Laboratory of Integration and Innovation of Classic Formula and Modern Chinese Medicine, Lunan Pharmaceutical Group Co. Ltd., Linyi, 276005, People’s Republic of China; 6Linyi Key Laboratory for Immunopharmacology and Immunotoxicology of Natural Medicine, Lunan Pharmaceutical Group Co. Ltd., Linyi, 273400, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming Liu, Email lmouc@ouc.edu.cn Jingchun Yao, Email yaojingchun@yeah.netBackground: Diabetic wounds are one of the most common complications of diabetes mellitus. Jingfang Granules (JFG), a combination of 11 herbs, has been clinically used for treating colds and the flu and for preventing various skin diseases.Purpose: The present study was designed to evaluate the therapeutic effect of JFG on diabetic wounds and to elucidate the associated mechanisms.Methods: JFG serum was prepared using Sprague-Dawley rats and the phytochemicals of JFG in the serum were identified using UHPLC-ESI-QE-Orbitrap-MS. A cell viability assay and cellular angiogenesis methods were performed to evaluate wound healing in vitro. Diabetic wounds were developed using streptozotocin-induced diabetic rats to investigate the efficacy of JFG on diabetic wounds in vivo. Network pharmacology analysis, molecular docking, and Western blot were performed to elucidate the potential mechanisms of JFG in diabetic wound healing.Results: JFG serum attenuated H2O2-induced and high glucose-induced oxidative damage, significantly reduced lipopolysaccharide-induced upregulation of inflammatory cytokines, and promoted angiogenesis in vitro. In diabetic rats, JFG effectively promoted wound healing, reduced blood glucose and lipid levels, and alleviated oxidative stress and inflammation. A total of 56 phytochemicals were identified in the JFG serum. Six core targets (AKT1, EGFR, MAPK3, MAPK1, IL6, and TNF) and the PI3K-AKT and MAPK signaling pathways were identified by network pharmacology analysis, which were further validated by subsequent experimental methods.Conclusion: JFG could accelerate diabetic wound healing by alleviating oxidative damage, suppressing inflammation, promoting angiogenesis, and regulating metabolic abnormalities, with involvement of the PI3K-AKT and MAPK signaling pathways. Keywords: jingfang granules, diabetic wounds, network pharmacology, MAPK, PI3K-AKT